PENERAPAN PASAL 303 KITAB UNDANG-UNDANG HUKUM PIDANA TERHADAP PEMILIK USAHA WARUNG INTERNET YANG MEMFASILITASI TEMPAT PERJUDIAN POKER FACE DI KOTA PEKANBARU - Wahyudi, Ilham; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Application of Article 303 Kitap Law Criminal Law against owners of internet cafes that provide games Poker Face in the city of Pekanbaru has not done well, the game is widely played by teenagers, such as students, the game Poker Face lots in the downtown area of advanced and more newcomers so many internet cafes that provide games Poker Face. In Pekanbaru city itself there are certain areas that many internet cafes with facilitating for Poker Face. for example is Marpoyan peaceful area of Pekanbaru. Tersebutlah background of the authors are interested to raise these issues in a research scientific work. The purpose of this thesis research: first to know penerpan Article 303 against the owner of the cafe with gambling facilities Poker Face. The second to determine the obstacles in the implementation of Article 303 of the cafe owners with facilities in the City Poker Face Pekanbaru.penulis conduct sociological juridical research is secondary data, to then proceed with research on primary data in the field, or in accordance with the reality of living in society. Authors conduct direct research on locations in the city of Pekanbaru, especially in Damai Marpoyan Kaharudin Nasution aim to obtain clear and complete picture about a situation or problem under study. From the research there are two main things that can be inferred. The first application of Article 303 Book of Law Criminal Law on regulating gambling has not done well, the application of that article menjerumus on providers that facilitate the game of Poker Face, for players Poker Face has not been touched in that Article, the curbing of gambling also has not done well, police just right the situation only to internet cafes are found to facilitate the Poker Face. The second constraint penerpan Article 303 Book of Law Criminal Law in curbing Poker Face is still constrained in its implementation system less effective, which only held controlling not given strict sanctions against internet cafes that facilitates a game of Poker Face. Suggestions authors in this study is the City Police Pekanbaru should give strict punishment for the community or individuals who open a business internet cafes and facilitated to be digunakanya as a game of Poker Face, so far only done policing alone, with tough sanctions the application of Article 303 Criminal Code oF Criminal Law to be implemented well, so it can be a lesson for other people not to open internet cafes and provides and facilitates for gambling Poker Face. Keywords: Application-Crime-Public Internet Gambling-Poker Face-Pekanbaru City Police